SYLLABUSES OF EDUCATIONAL DISCIPLINES: MODERN APPROACHES TO THE FORMATION OF THE CONTENT OF ENGINEERING SPECIALISTS’ TRAINING - Batechko, Nina; Pantaliyenko, Lyudmyla (Educological discourse, 2020)
In the article the authors consider modern approaches to the formation of the content of training of engineering specialists on the example of modelling the syllabi of academic disciplines. A comparative analysis of current trends in the content of professional training of engineering personnel in institutions of higher technical education in Ukraine, Western Europe and China. It is noted that one of the main shortcomings of domestic higher education is still its inconsistency with the requirements of the labour market and the lag of technical training from scientific and technological progress. The latter encourages the revision of another strategic involvement of training – the formation of professional competencies of future professionals, and hence the formation of a new content of training for future engineers. An example of such attempts is the introduction of syllabuses in the educational process of higher education. The creation of information and educational networks has globalized this problem and led to the need to realize it at a new innovative level. The article focuses on the definitive analysis of the researched problem and on the basic principles of syllabus construction, which are based on the competence approach. It is noted that the main task of this analysis is to study the substantive nuances between the syllabi of academic disciplines and their work programs, why and for whom this document is prepared and whether it is right at all. Emphasis is placed on the basic principles of construction of syllabi of academic disciplines, according to which they can be distinguished from work programs. As a fundamental principle, access to learning outcomes is highlighted, which should be expressed through the levels of competencies of graduates. Thus, through educational activities, the opportunity to design the future professional activity of the student is realized, and as a result to consider the competence acquired in the learning process. The structural components of syllabuses of academic disciplines are considered. The structure of the syllabus of the discipline in terms of components and a specific example of its modelling have been provided.